The effect of cellular environment and p53 status on the mode of action of the platinum derivative LA-12 - Roubalová, Eva; Kvardová, Veronika; Hrstka, Roman; Borilová, Sárka; Michalová, Eva; Dubská, Lenka; Müller, Petr; Sova, Petr; Vojtesek, Borivoj (Investigational new drugs, 2010)
In this study, we characterized the effects of LA-12 on tumor cell lines possessing wild type p53 and on p53-deficient/mutant cell lines and the results were compared to those obtained using cisplatin. We have determined changes of p53 levels, of its transcriptional activity, of its posttranscriptional modifications and the effect of the treatment on the cell cycle, on the induction of apoptosis and on gene expression. LA-12 induces weak accumulation of both transcriptionally active p53 tumor suppressor and of p21(WAF1/CIP1) protein. LA-12 and cisplatin also significantly differ in their effects on apoptosis and cell cycle and on gene expression spectra in studied cell lines. LA-12 induces higher apoptosis levels in comparison with those induced by cisplatin, especially in p53-deficient H1299 cells and in MCF-7DD cells with transcriptionally inactive p53. We suggest that LA-12-mediated apoptosis is not fully dependent on p53. This confirms the therapeutic potential of LA-12 as a more potent cytostatic agent for both tumor cells expressing wild type p53 and for p53-deficient or mutant cells.
Keywords: nádorový supresorový protein p53; Cell Cycle; nádorové buněčné linie; apoptóza; Cyclin-Dependent Kinase Inhibitor p21; regulace genové exprese u nádorů; Cisplatin; cisplatina; amantadin; Organoplatinum Compounds; mutace; Tumor Suppressor Protein p53; Cell Line, Tumor; Amantadine; Antineoplastic Agents; buněčný cyklus; protinádorové látky; Apoptosis Regulatory Proteins; Humans; Gene Expression Regulation, Neoplastic; Mutation; organoplatinové sloučeniny; inhibitor p21 cyklin-dependentní kinasy; Genes, p53; proteiny regulující apoptózu; geny p53; lidé; Apoptosis